Long-range transcriptional interference in E. coli used to construct a dual positive selection system for genetic switches - Hoffmann, Stefan A. (Nucleic Acids Res, 2016)
We have investigated transcriptional interference between convergent genes in E. coli and demonstrate substantial interference for inter-promoter distances of as far as 3 kb. Interference can be elicited by both strong σ(70) dependent and T7 promoters. In the presented design, a strong promoter driving gene expression of a ‘forward’ gene interferes with the expression of a ‘reverse’ gene by a weak promoter. This arrangement allows inversely correlated gene expression without requiring further regulatory components. Thus, modulation of the activity of the strong promoter alters expression of both the forward and the reverse gene. We used this design to develop a dual selection system for conditional operator site binding, allowing positive selection both for binding and for non-binding to DNA. This study demonstrates the utility of this novel system using the Lac repressor as a model protein for conditional DNA binding, and spectinomycin and chloramphenicol resistance genes as positive selection markers in liquid culture. Randomized LacI libraries were created and subjected to subsequent dual selection, but mispairing IPTG and selection cues in respect to the wild-type LacI response, allowing the isolation of a LacI variant with a reversed IPTG response within three rounds of library generation and dual selection.